The Precision of National Income Estimates - Stone, Richard; Champernowne, D. G.; Meade, J. E. (Review of Economic Studies, 1942)
Richard Stone, D. G. Champernowne, J. E. Meade; The Precision of National Income Estimates, The Review of Economic Studies, Volume 9, Issue 2, 1 July 1942,